ETNOGRAFI KOMUNIKASI DALAM TRADISI DOA PADANG DI DESA PADANG KUNIK KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Sari, Rajunda; Mustaqimmah, Nurul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The Doa Padang Tradition is a cultural heritage or tradition carried out by the community of Padang Kunik Village, Pangean District, Kuantan Singingi Regency. The purpose of this research is to analyze the communicative situation, communicative events, and communicative action related to the Doa Padang tradition. This type of research uses a qualitative method accompanied by a communication ethnography approach. There were seven informants in this study, consisting of the Village Head, Village Officials, Tuo Banjar, Farmers or community members, youth and young women. The results of the research show that the communicative situation in the Doa Padang tradition consists of the location where the tradition is carried out. Communicative events in the Doa Padang tradition include the type of event, event topic, massage from, massage content, sequence of actions, interaction rules, and interpretation norms in this tradition. The communicative actions of the Doa Padang tradition consist of verbal messages and non-verbal messages. Keywords: Etnography of Communication, Doa Padang Tradition, Kuantan Singingi Tradition